Reverse Active Modification Method of Tooth Profile for RV Reducer Cycloidal Gear - Xiaotao An; Tianxing Li; Chunrong Xing; Guofeng Wang; Meng Tian (Jixie chuandong, 2019)
Tooth profile modification design is a key link in the design and manufacture of cycloidal gear of RV reducer. However, the influence relation of tooth profile error and motion accuracy on tooth profile shape has not been considered in the current design of cycloidal gear profile modification. A new method of cycloidal gear profile inverse active modification considering the influence of tooth profile error and transmission error is proposed. Through the contact analysis of the cycloidal pin wheel of RV transmission, the modification coefficient ac, constant coefficient b and mismatch reference point meshing phase angle <alternatives>φ0 <?fx-imagestate width="3.38666677" height="4.40266657"?> <?fx-imagestate width="3.38666677" height="4.40266657"?> </alternatives> of the parabolic modification method are taken as the modification variables of the tooth profile, and the mathematical model of the reverse modification of the tooth profile is established with the minimum transmission error as the objective function. Finally, the accuracy of the RV transmission is satisfied, the best tooth profile is obtained. The method considers the interaction between the shape change of cycloid tooth profile and the meshing characteristics and transmission accuracy.While ensuring the meshing characteristics and motion accuracy, the design profile of cycloid wheel is obtained, which is more in line with the engineering practice, guarantees the assembly process of cycloid pin wheel pair of RV reducer, and pre-controls the transmission performance of RV and corrects the profile. It provides theoretical and technical support for improving the quality and accuracy of motion.